Digital economy : emerging technologies and business innovation : second International Conference, ICDEc 2017, Sidi Bou Said, Tunisia, May 4-6, 2017, Proceedings /: emerging technologies and business innovation : second International Conference, ICDEc 2017, Sidi Bou Said, Tunisia, May 4-6, 2017, Proceedings. (2017) - Unknown
No abstract available